Full set of relaxation constants for 174Yb level (6s6p) 3P1 in collisions with rare gases. (1st April 2021) - Rubtsova, N N; Khvorostov, E B; Kochubei, S A; Reshetov, V A
Abstract: For the first time, a complete set of decay parameters, due to collisions of 174 Yb atoms with noble gas atoms and with ytterbium atoms, was experimentally found for the 174 Yb (6s6p) 3 P1 level. The method of stimulated photon echo with special angles between the polarization vectors of light pulses forming an echo at the 174 Yb (6s 2 ) 1 S0 —(6s6p) 3 P1 transition (type 0 ↔ 1 ) is used. For each buffer gas of He, Ne, Ar, Kr, Xe, and Yb, the decay rate constants of population, orientation and alignment for the collision destruction of the 3 P1 level of 174 Yb atoms are determined. All the decay rates demonstrated their linear increase with a buffer gas pressure, and the corresponding relaxation constants are determined. Each of the indicated relaxation constants, as well as the difference between the alignment and orientation relaxation constants, increases with the increasing buffer gas mass.